Article 23 Income Tax Calculation System for Expedition Services: Study at one of the National Express Delivery and Logistics Service Companies in Bandung City - Aprilia, Sani; Wahyudi, Heri (Center of Research, STIE Pasundan, Bandung, Indonesia., 2023)
Correct and accurate tax calculations can make it easier for company owners to know the amount of deductions paid and make the right decisions that company owners will make for the business they are involved in in the future. Moreover, with the correct tax deductions, they can increase state treasury income appropriately to avoid errors or fraud in the reporting. Calculating income tax (PPh), article 23 for expedition services is accompanied by a large amount of goods delivery transaction data based on available delivery services, which causes errors in the calculations due to differences in the delivery services selected. The design of the Income Tax (PPh) Calculation System Article 23 for one of the national express delivery and logistics service companies in Bandung is made on a web basis. The research method used is the descriptive method with data collection techniques in the form of observation, interviews, and literature study, and was designed using the OOAD (Object Oriented Analysis Design) system development method, namely the process of analysis, design, and implementation of the system based on objects. The programming language used is PHP with the PHPMyAdmin database. It is hoped that the design of the PPh 23 tax calculation system will make it easier for companies to input the necessary data, make the calculation process easier because it is done automatically and will be more accurate, and make it easier to print reports if one day they need a report in hard copy form.